Aortic arch calcification, procedural times, and outcomes of endovascular treatment in patients with acute ischemic stroke - Qureshi, Adnan I (Zeenat Qureshi Stroke Institute, 2014)
OBJECTIVE: To determine the frequency of aortic arch calcification and it’s relationship with procedural times, angiographic recanalization, and discharge outcomes in acute ischemic stroke patients undergoing endovascular treatment. METHODS: The thoracic component of computed tomographic (CT) angiogram were reviewed by an independent reviewer to determine presence of any calcification; and the severity of calcification was graded as follows: mild, single small calcifications; moderate, multiple small calcifications; or severe, one or more large calcifications. RESULTS: Aortic arch calcification was present in 120 (62.4%) of 188 patients and severity was graded as mild (n=24), moderate (n=44), and severe (n=52). Compared with patients without calcification, the mean intracranial access time (minutes ± SD) was similar among patients with aortic arch calcification (70 ± 31 versus 64 ± 31, p=0.9). The mean time intracranial access time increased with increasing severity of aortic arch calcification (61±27, 67±29, and 74±34, p=0.3). Patients with aortic arch calcification had similar rates of complete or partial recanalization [85 (71%) versus 50 (76%)], p=0.6) but lower rates of favorable outcomes [modified Rankin scale 0–2] at discharge 27 (22%) versus 26 (39%), p=0.02). CONCLUSIONS: A high proportion of acute ischemic stroke patients have aortic arch calcification which is associated with lower rates of favorable outcome following endovascular treatment. ABBREVIATIONS: SD: standard deviation ICH: intracerebral hemorrhage NIHSS: National Institutes of Health Stroke Scale TIA: transient ischemic attack ICH: intracerebral hemorrhage mRS: modified Rankin scale